Effect-directed analysis of cold-pressed hemp, flax and canola seed oils by planar chromatography linked with (bio)assays and mass spectrometry. (15th November 2015) - Teh, Sue-Siang; Morlock, Gertrud E.
Highlights: Single effective components were detected in hemp, flax and canola oilseeds. Chromatogram zones were directly linked to effective zones. Enzymatic, bacterial and yeast cell assays were employed. Esterase inhibiting, estrogen-effective and antimicrobial compounds were discovered. Targeted mass spectrometry to characterize bioactive compounds. Abstract: Cold-pressed hemp, flax and canola seed oils are healthy oils for human consumption as these are rich in polyunsaturated fatty acids and bioactive phytochemicals. However, bioactive information on the food intake side is mainly focused on target analysis. For more comprehensive information with regard to effects, single bioactive compounds present in the seed oil extracts were detected by effect-directed assays, like bioassays or an enzymatic assay, directly linked with chromatography and further characterized by mass spectrometry. This effect-directed analysis is a streamlined method for the analysis of bioactive compounds in the seed oil extracts. All effective compounds with regard to the five assays or bioassays applied were detected in the samples, meaning also bioactive breakdown products caused during oil processing, residues or contaminants, aside the naturally present bioactive phytochemicals. The investigated cold-pressed oils contained compounds that exert antioxidative, antimicrobial, acetylcholinesterase inhibitory and estrogenic activities. This effect-directed analysis can be recommended for bioactivity profiling of food to obtain profound effect-directed information on the food intake side.